Use of crude, FML and rK39 antigens in ELISA to detect anti-Leishmania spp. antibodies in Felis catus - Neto, Luiz da Silveira; Vicente Sobrinho, Ludmila Silva; Martins, Camille Oliveira; Machado, Rosangela Zacarias [UNESP]; Marcondes, Mary [UNESP]; Felix de Lima, Valeria Marcal [UNESP] (Elsevier B.V., 2011)
Visceral leishmaniasis is a disease caused by Leishmania (Leishmania) chagasi and represents a serious public health problem. The dog is the main urban reservoir of the disease: however, investigations regarding the occurrence and epidemiological importance of leishmaniasis in cats have recently been initiated. This study aimed to detect cats seropositive for Leishmania spp. using different antigens. Additional studies were performed using sera from cats with Toxoplasma gondii (n = 15) to evaluate cross-reactivity. Serum samples (n = 113) from cats living in the town of Aracatuba, State of São Paulo, Brazil, an endemic area for human and canine visceral leishmaniasis, were tested by indirect ELISA using different antigens: crude (CAG-ELISA), fucose-mannose ligand (FML-ELISA) and K39 (rK39-ELISA). Anti-Leishmania spp. antibodies were detected in 23.0% of samples evaluated by CAG-ELISA, 13.3% by FML-ELISA and 15.9% by RK39-ELISA. Only reactive sera in all three tests were considered truly positive. No disagreement occurred among the tests (p <0.05). Serum samples seropositive for toxoplasmosis tested by CAG-ELISA were negative, but one sample (6.7%) was positive for FML-ELISA and rK39-ELISA suggesting a cross-reaction between these antigens and anti-T. gondii antibodies. These findings indicate the occurrence of feline leishmaniasis in Aracatuba. Further studies are required to clarify the role of cats in the epidemiological cycle of leishmaniasis. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diagnosis; Cat; Leishmaniasis; Serology; Toxoplasma